Automated system measuring triple oxygen and nitrogen isotope ratios in nitrate using the bacterial method and N2O decomposition by microwave discharge. (6th November 2016) - Hattori, Shohei; Savarino, Joel; Kamezaki, Kazuki; Ishino, Sakiko; Dyckmans, Jens; Fujinawa, Tamaki; Caillon, Nicolas; Barbero, Albane; Mukotaka, Arata; Toyoda, Sakae; Well, Reinhard; Yoshida, Naohiro
Abstract : Rationale: Triple oxygen and nitrogen isotope ratios in nitrate are powerful tools for assessing atmospheric nitrate formation pathways and their contribution to ecosystems. N2 O decomposition using microwave‐induced plasma (MIP) has been used only for measurements of oxygen isotopes to date, but it is also possible to measure nitrogen isotopes during the same analytical run. Methods: The main improvements to a previous system are (i) an automated distribution system of nitrate to the bacterial medium, (ii) N2 O separation by gas chromatography before N2 O decomposition using the MIP, (iii) use of a corundum tube for microwave discharge, and (iv) development of an automated system for isotopic measurements. Three nitrate standards with sample sizes of 60, 80, 100, and 120 nmol were measured to investigate the sample size dependence of the isotope measurements. Results: The δ 17 O, δ 18 O, and Δ 17 O values increased with increasing sample size, although the δ 15 N value showed no significant size dependency. Different calibration slopes and intercepts were obtained with different sample amounts. The slopes and intercepts for the regression lines in different sample amounts were dependent on sample size, indicating that the extent of oxygen exchange is also dependent on sample size. The sample‐size‐dependent slopes and intercepts were fitted using natural log (ln) regression curves, and the slopes and intercepts can be estimated to apply to any sample size corrections. When using 100 nmol samples, the standard deviations of residuals from the regression lines for this system were 0.5‰, 0.3‰, and 0.1‰, respectively, for the δ 18 O, Δ 17 O, and δ 15 N values, results that are not inferior to those from other systems using gold tube or gold wire. Conclusions: An automated system was developed to measure triple oxygen and nitrogen isotopes in nitrate using N2 O decomposition by MIP. This system enables us to measure both triple oxygen and nitrogen isotopes in nitrate with comparable precision and sample throughput (23 min per sample on average), and minimal manual treatment. Copyright © 2016 John Wiley & Sons, Ltd.